Senolytic treatment with dasatinib and quercetin does not improve overall influenza responses in aged mice - Torrance, Blake L.; Cadar, Andreia N.; Martin, Dominique E.; Panier, Hunter A.; Lorenzo, Erica C.; Bartley, Jenna M.; Xu, Ming; Haynes, Laura (Frontiers in Aging, 2023)
Age is the greatest risk factor for adverse outcomes following influenza (flu) infection. The increased burden of senescent cells with age has been identified as a root cause in many diseases of aging and targeting these cells with drugs termed senolytics has shown promise in alleviating many age-related declines across organ systems. However, there is little known whether targeting these cells will improve age-related deficits in the immune system. Here, we utilized a well characterized senolytic treatment with a combination of dasatinib and quercetin (D+Q) to clear aged (18-20mo) mice of senescent cells prior to a flu infection. We comprehensively profiled immune responses during the primary infection as well as development of immune memory and protection following pathogen reencounter. Senolytic treatment did not improve any aspects of the immune response that were assayed for including: weight loss, viral load, CD8 T cell infiltration, antibody production, memory T cell development, or recall ability. These results indicate that D+Q may not be an appropriate senolytic to improve aged immune responses to flu infection.